Conditioned Serum Enhances the Chondrogenic and Immunomodulatory Behavior of Mesenchymal Stem Cells - Blázquez, Rebeca; Sánchez-Margallo, Francisco Miguel; Reinecke, Julio; Álvarez, Verónica; López, Esther; Marinaro, Federica; Casado, Javier G. (Frontiers in Pharmacology, 2019)
Osteoarthritis is one of the most common chronic health condition associated with pain and disability. Advanced therapies based on mesenchymal stem cells have become valuable options for the treatment of these pathologies. Conditioned serum (CS) has been used intraarticularly for osteoarthritic patients. In this work we hypothesized that the rich content on anti-inflammatory proteins and growth factors of CS may exert a beneficial effect on the biological activity of adipose-derived mesenchymal stem cells (hAdMSCs). In vitro studies were designed using hAdMSCs co-cultured with CS at different concentrations (2.5%, 5% and 10%). Chondrogenic differentiation assays and immunomodulatory experiments using in vitro stimulated lymphocytes were performed. Our results demonstrated that CS significantly enhanced the differentiation of hAdMSCs towards chondrocytes. Moreover, hAdMSCs pre-sensitized with CS reduced the lymphocyte proliferation as well as their differentiation towards activated lymphocytes. These results suggest that in vivo co-administration of CS and hAdMSCs may have a beneficial effect on the therapeutic potential of hAdMSCs. Moreover, these results indicate that intra-articular administration of CS might influence the biological behavior of resident stem cells increasing their chondrogenic differentiation and inherent immunomodulatory activity. To our knowledge, this is the first in vitro study reporting this combination.